A Strategy for Strengthening Ecotourism Based on the Dayak Meratus’s Local Wisdom Governance for Ecosystem Conservation - Ahmad Ahmad; Mutiani Mutiani; Muhammad Asraf Abdullah; Rifiana Rifiana; Nurmelati Septiana (Universitas Lambung Mangkurat, 2026)
The Meratus Mountains in South Kalimantan feature a landscape of significant ecological, social, and cultural importance for the sustainability of the Dayak Meratus Indigenous Community. This area also represents a living space managed through ecological knowledge and customary institutions that have been passed down from generation to generation. However, the area has evolved into an ecotourism destination that is popular among people looking to spend their vacations. This article aims to analyze strategies for strengthening ecotourism based on the Dayak Meratus’s local wisdom as an approach that can reconcile ecosystem conservation goals with the recognition and strengthening of indigenous peoples’ rights. The research employs a descriptive qualitative approach through a literature review and document analysis of indexed journal articles. Data were analyzed using thematic content analysis to identify relevant patterns, practices, and governance strategies. The study’s findings indicate that the local wisdom of the Dayak Meratus—reflected in the management of pamali forests, the practice of shifting cultivation (manugal), the aruh ritual, and the institutional roles of the damang and balian—not only serves cultural functions but also forms community-based conservation mechanisms. Based on these findings, efforts to strengthen ecotourism are directed through four main strategies, namely: strengthening customary institutions as co-managers of the area; accelerating the recognition of customary forests and village forests as the basis for partition zoning. Based on these findings, efforts to strengthen ecotourism are guided by four main strategies: strengthening indigenous institutions as co-managers of the area; accelerating the recognition of indigenous forests and village forests as the foundation for participatory zoning; integrating traditional ecological knowledge into tourism interpretation and conservation education; and developing mechanisms for the equitable distribution of economic benefits through community-based enterprises. This study confirms that ecotourism rooted in local wisdom and managed through collaborative governance has the potential to serve as an instrument for strengthening ecosystem conservation while simultaneously enhancing participation, economic self-reliance, and recognition of the rights of indigenous communities. Thus, this model can be developed as a more inclusive, equitable, and sustainable conservation approach in the Meratus Mountains region.